Analysis of Teacher Professionalism in Implementing the Independent Learning Program in Islamic Educational Units - Ali Yusron (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2025)
This study examines teacher professionalism in the implementation of the Merdeka Belajar (Freedom to Learn) program within Islamic educational institutions. The Merdeka Belajar initiative, launched by the Ministry of Education, Culture, Research, and Technology, seeks to foster a flexible and inclusive learning ecosystem, empower teachers to design curricula responsive to students’ characteristics, and enhance the overall quality of education. Employing a qualitative approach with a case study design, this research utilizes in-depth interviews, classroom observations, and document analysis as its primary data collection techniques. The study focuses on identifying the challenges teachers encounter in designing, implementing, and evaluating instruction aligned with Merdeka Belajar principles, as well as the factors influencing teacher professionalism, including leadership support, professional development opportunities, and resource availability. The findings reveal that while most teachers have adopted the Merdeka Belajar framework, significant challenges persist regarding conceptual understanding, teacher preparedness, and resource constraints. These results underscore the necessity for more comprehensive training programs and stronger institutional support to optimize the implementation of the Merdeka Belajar program, particularly within Islamic educational contexts